Efficiency of combined action of antimicrobial preparations against poly-resistant strains of conditionally-pathogenic bacteria isolated from wounds of surgery patients - T. V. Sklyar; K. V. Lavrentievа; O. M. Rudas; О. V. Bilotserkivska; N. V. Kurahina; M. G. Papiashvili; O. A. Lykholat (Regulatory Mechanisms in Biosystems, 2020)
The strategy of use of combination therapy of antibacterial preparations is being broadly introduced to clinical practice to fight bacterial infections caused by poly-resistant strains of microorganisms. From the wounds of surgery patients, we isolated 67 clinical strains of conditionally-pathogenic bacteria identified as Staphylococcus aureus, S. epidermidis, Escherichia coli, Klebsiella pneumoniaе, Proteus vulgaris, Proteus mirabilis, Pseudomonas aeruginosa. Using disk diffusion method, the isolated bacterial strains were found to be most resistant to penicillin preparations: ampicillin, oxacillin, amoxicillin/clavulanat; tetracycline and cephalosporin of the II generation – cefoxitin. The percentage of strains insusceptible to these antibacterial preparations accounted for 65.0%. The division of antibiotic-resistant cultures regarding phenotype groups according to the level of their antibiotic resistance allowed determination of 4 PDR-, 8 XDR- and 14 MDR-strains. During the studies on experimental determining of MIC of antibiotic and antiseptics in the condition of applying them as monopreparations against isolated bacterial cultures, we saw significant exceess in the threshold values of MIC, and, first of all, regarding pandrug-resistant and extensive drug-resistant clinical microbial isolates. Use of combinations of antibacterial preparations was found to show the synergic effect of antibiotics (ceftriaxone, ofloxacin, gentamicin) and antiseptics (chlorhexidine, decasan), which is expressed in simultaneous decrease in MIC of each of the tested preparations by 2–8 times compared with their isolative application. Such combinatory approach regarding simultaneous application of antibacterial preparations may be considered as one of the most promising ways to combat poly-resistant clinical isolates of conditionally-pathogenic microorganisms and to offer a new strategic approach to prevention of spread of antibiotic resistance as a phenomenon in medical practice.